Oxidative damage of U937 human leukemic cells caused by hydroxyl radical results in singlet oxygen formation - Rác, Marek; Křupka, Michal; Binder, Svatopluk; Sedlářová, Michaela; Matušková, Zuzana; Raška, Milan; Pospíšil, Pavel (PloS one, 2015)
The exposure of human cells to oxidative stress leads to the oxidation of biomolecules such as lipids, proteins and nuclei acids. In this study, the oxidation of lipids, proteins and DNA was studied after the addition of hydrogen peroxide and Fenton reagent to cell suspension containing human leukemic monocyte lymphoma cell line U937. EPR spin-trapping data showed that the addition of hydrogen peroxide to the cell suspension formed hydroxyl radical via Fenton reaction mediated by endogenous metals. The malondialdehyde HPLC analysis showed no lipid peroxidation after the addition of hydrogen peroxide, whereas the Fenton reagent caused significant lipid peroxidation. The formation of protein carbonyls monitored by dot blot immunoassay and the DNA fragmentation measured by comet assay occurred after the addition of both hydrogen peroxide and Fenton reagent. Oxidative damage of biomolecules leads to the formation of singlet oxygen as conformed by EPR spin-trapping spectroscopy and the green fluorescence of singlet oxygen sensor green detected by confocal laser scanning microscopy. It is proposed here that singlet oxygen is formed by the decomposition of high-energy intermediates such as dioxetane or tetroxide formed by oxidative damage of biomolecules.
Keywords: Electron Spin Resonance Spectroscopy; nádorové buněčné linie; Malondialdehyde; karbonylace proteinů; malondialdehyd; Comet Assay; lidé; Singlet Oxygen; Microscopy, Confocal; Hydroxyl Radical; hydroxylový radikál; Chromatography, High Pressure Liquid; peroxid vodíku; Oxidative Stress; železo; Cell Line, Tumor; Lipid Peroxidation; vysokoúčinná kapalinová chromatografie; konfokální mikroskopie; Iron; Humans; viabilita buněk; Cell Survival; elektronová paramagnetická rezonance; Protein Carbonylation; kometový test; oxidační stres; singletový kyslík; leukemie; Hydrogen Peroxide; peroxidace lipidů; Leukemia